2023
DOI: 10.1515/jpm-2022-0371
|View full text |Cite
|
Sign up to set email alerts
|

Comparative clinical and placental pathologic characteristics in pregnancies with and without SARS-CoV-2 infection

Abstract: Objectives To compare the clinical and morphological characteristics of the “mother-placenta-fetus” system in high risk pregnant women of three groups: no SARS-CoV-2 infection, mild SARS-CoV-2 infection, and severe SARS-CoV-2 infection. Methods A case-control study was performed for all deliveries, at 28 weeks’ gestation or greater, who had standard indications for placental pathologic examination. Three groups were formed: (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 50 publications
1
1
0
Order By: Relevance
“…This observation was made for women who had mild symptoms [18]. Likewise, one study revealed that even though perinatal HIE was more common in the group with severe COVID-19 course, there were no differences between the group with mild disease and the control group in terms of perinatal outcomes [19]. In our study, HIE grade 1 was the most frequent occurrence in the COVID-19 group versus the vaccine and control groups.…”
Section: Discussionsupporting
confidence: 57%
“…This observation was made for women who had mild symptoms [18]. Likewise, one study revealed that even though perinatal HIE was more common in the group with severe COVID-19 course, there were no differences between the group with mild disease and the control group in terms of perinatal outcomes [19]. In our study, HIE grade 1 was the most frequent occurrence in the COVID-19 group versus the vaccine and control groups.…”
Section: Discussionsupporting
confidence: 57%
“…Due to both the placental and perinatal hypoxic-ischemic events, the fetus is exposed to higher risks of developing congenital malformations or growth retardations [54]. Furthermore, the ischemic placental events are assumed to be correlated with intestinal atresia (more frequently localized on the jejunal, ileal, and colonic segments), but no statistical significance was found when the incidences were compared with the pre-COVID-19 era and COVID-19 pandemic era in the pregnant females having hypoxemic episodes due to COVID-19 infection [55].…”
Section: Discussionmentioning
confidence: 99%